A mixed‐methods study of the management of hearing loss associated with otitis media with effusion in children with Down syndrome. (8th October 2018) - Hall, Amanda; Pryce, Helen; Bruce, Iain A.; Callery, Peter; Lakhanpaul, Monica; Schilder, Anne G. M.
Abstract : Objectives: To scope current service provision across England for management of otitis media with effusion and hearing loss in children with Down syndrome; to explore professional decision‐making about managing otitis media with effusion and hearing loss; and to explore patient and public views on the direction of future research. Design: Mixed methods including a service evaluation of NHS clinical practice through a structured telephone survey; a qualitative study of professional decision‐making with in‐depth interviews collected and analysed using grounded theory methods; patient/public involvement consultations. Participants: Twenty‐one audiology services in England took part in the evaluation; 10 professionals participated in the qualitative study; 21 family members, 10 adults with Down syndrome and representatives from two charities contributed to the consultations. Results: There was variation across services in the frequency of routine hearing surveillance, approaches to managing conductive hearing loss in infancy and provision of hearing aids and grommets. There was variation in how professionals describe their decision‐making, reflecting individual treatment preferences, differing approaches to professional remit and institutional factors. The consultations identified that research should focus on improving practical support for managing the condition and supporting decision‐making about interventions. Conclusions: There is system‐level variation in the provision of services and individual‐level variation in how professionals make clinical decisions. As a consequence, there is inequity of access to hearing health care for children with Down syndrome. Future research should focus on developing core outcomes for research and care, and on improving decision support for families.